Professional Divisions (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1923)
Professional Divisions I-Institute of Metals Division* GEORGE K ELLIOTT, Chairman GEORGE C STONE, Vice-chairman WILLIAM M CORSE, Secretary-treasurer Executive Committee D K CRAMPTON SAMUEL L HOYT R I, SUHL W K FRANK ZAY JEFFRIES A E WHITE H W GILLETT H C JENNISON R F WOOD STANISLAUS SKOWRONSKI II-Petroleum Division F JULIUS FOHS, Chairman EDWARD L ESTABROOK, Vice-chairman C P WATSON, Secretary-treasurer